2021
DOI: 10.3390/math9090943
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Study on the Behavior of Improved Beam T-Junctions Modeling for the Characterization of Tubular Structures, Based on Artificial Neural Networks Trained with Finite Element Models

Abstract: The actual behavior of welded T-junctions in tubular structures depends strongly on the topology of the junction at the joint level. In finite element analysis, beam-type elements are usually employed due to their simplicity and low computational cost, even though they cannot reproduce the joints topologies and characteristics. To adjust their behavior to a more realistic situation, elastic elements can be introduced at the joint level, whose characteristics must be determined through costly validations. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This aspect was also analyzed in [2], in which the authors concluded that the beamtype elements "were simply not designed to take into account and reproduce the behavior of real joints, since all the elements that reach the same joint are joined in a single infinitely rigid node". The main drawback of beam-element-type modeling is represented in Figure 3, where the same beam T-junction model is obtained for both T1 and T2 real junctions, despite the fact that they have significant topological differences at the joint level with consequent behavioral differences between both junctions.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This aspect was also analyzed in [2], in which the authors concluded that the beamtype elements "were simply not designed to take into account and reproduce the behavior of real joints, since all the elements that reach the same joint are joined in a single infinitely rigid node". The main drawback of beam-element-type modeling is represented in Figure 3, where the same beam T-junction model is obtained for both T1 and T2 real junctions, despite the fact that they have significant topological differences at the joint level with consequent behavioral differences between both junctions.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect was also analyzed in [2], in which the authors concluded that the beam-type elements "were simply not designed to take into account and reproduce the behavior of real joints, since all the elements that reach the same joint are joined in a single infinitely rigid node".…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations